2003
DOI: 10.1128/jvi.77.15.8378-8385.2003
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Langerhans Cells in Human Papillomavirus Type 16-Infected Skin Is Associated with E6-Mediated Down Regulation of E-Cadherin

Abstract: Human papillomavirus type 16 (HPV16) is an oncogenic virus that causes persistent infections in cervical epithelium. The chronic nature of HPV16 infections suggests that this virus actively evades the host immune response. Intraepithelial Langerhans cells (LC) are antigen-presenting cells that are critical in T-cell priming in response to viral infections of the skin. Here we show that HPV16 infection is directly associated with a reduction in the numbers of LC in infected epidermis. Adhesion between keratinoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
114
1
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(127 citation statements)
references
References 57 publications
5
114
1
7
Order By: Relevance
“…2) The E6 oncoprotein inhibits the interactions between epithelial cells and DCs [58], possibly accounting for the depletion of DCs observed in the HPV-infected cervical epithelium [59]. An E6 oncoprotein-mediated reduction in expressed interleukin-8 (IL-18) CD8 + was also observed [60].…”
Section: Humoral Immune Responses and Cell-mediated Immune Responses mentioning
confidence: 99%
See 4 more Smart Citations
“…2) The E6 oncoprotein inhibits the interactions between epithelial cells and DCs [58], possibly accounting for the depletion of DCs observed in the HPV-infected cervical epithelium [59]. An E6 oncoprotein-mediated reduction in expressed interleukin-8 (IL-18) CD8 + was also observed [60].…”
Section: Humoral Immune Responses and Cell-mediated Immune Responses mentioning
confidence: 99%
“…Another animal study, which used a long peptide (E7 [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] ) and the DC-activating adjuvant ODN-CpG, has identified that vaccination with a longer peptide containing CTL and Th cell epitopes, and ODN-CpG represents a promising strategy against MHC-I deficient tumors. This study also investigated the efficacy of cellular vaccines based on ex vivo cultured DCs pulsed with either minimal CTL (E7 [49][50][51][52][53][54][55][56][57] ) epitope or longer CTL (E7 [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] ) epitopes, and then matured with ODNCpG. The use of ex vivo cultured DCs is particularly suitable f...…”
Section: Vaccine Deliverymentioning
confidence: 99%
See 3 more Smart Citations